Funktionswörter als Indikatoren für diskursspezifische Argumentationsstrukturen im printmedialen Diskurs über den fünften Sachstandsbericht des Weltklimarates - Kammermann, Nadine (Linguistik Online, 2018)
This study aims to explore how Swiss print media convey climate change to laypeople. Due to the subjects' complexity and scope, its mediation can result in difficulties. A corpus of articles on the IPCC (Intergovernmental Panel on Climate Change) provides an insight into discursive argumentation structures. Corpus-driven collected function word clusters enable to identify argumentative schemes in the media discourse. The qualitative analysis of these argumentative clusters reveals the significance of several actors, particularly administrative and cognitive authorities. Furthermore, prominent are institutional features and differences in scientific and everyday media argumentation norms.